Heart wisdom: the search beyond head knowledge - Frank Ople (Environmental Association of Southern Africa, 1987)
The thesis is proposed that the conventional approaches to the teaching of science, and particularly biology, has failed to place sufficient emphasis on the affective domain. The concept of knowledge is examined and suggestions are made as to how the situation might be improved.